Abnormalities of Resting-State Electroencephalographic Microstate in Rapid Eye Movement Sleep Behavior Disorder - Peng, Anjiao; Wang, Ruien; Huang, Jiamin; Wu, Haiyan; Chen, Lei (Frontiers in Human Neuroscience, 2021)
Objective: Rapid eye movement (REM) Sleep Behavior Disorder (RBD) is a disease characterized by dream enactment and is commonly a harbinger to neurodegeneration diseases. The aim of this study is to explore the quasi-stable topological structure of the brain in RBD by analyzing resting-state electroencephalography (EEG) microstates. Methods: We enrolled 22 participants with RBD and 46 age and sex- matched healthy controls (HCs). After the resting-state EEG recording were acquired, EEG microstate features were analyzed to assess the functional networks of all participants. Results: Significant differences of the brain topological structure and temporal characteristics of sub-second brain activity were found between the RBD and HCs. The RBD group had a longer average duration of microstate A and microstate D. Microstate B contributed more, while microstate D contributed significantly less in RBD group when compared with HCs. Furthermore, the average duration and proportion of microstate D were negatively correlated with the RBDQ-HK score. Conclusions: The results of this study indicate that the microstate dynamics is disturbed in RBD, which might jeopardize the flexibility and adaptability of the brain. Microstates are potential biomarkers to explore the early abnormality of the electro-physiological features of neurodegeneration diseases.